'Real experiences which increase empathy' – a preliminary exploration of the utility of an audio archive describing parents' and clinicians' experiences of stillbirth. Issue 1 (2nd January 2019) - Beck, Emma; Gibson, Nicola; Heazell, Alexander
Abstract: Perinatal death has an enduring effect on parents which is altered by their experience of care. However, professionals frequently report feeling underprepared to care for bereaved parents. This study evaluated parents' and professionals' experiences of using an audio archive of experiences of perinatal deaths (www.stillbirthstories.org ) using a self-reported questionnaire. Eighty-three percent of parents and the public ( n  = 33) found listening to the archive helpful, with no negative responses. Fifty-four percent stated that it changed how they felt about having a perinatal death, increasing the proportion of respondents who felt supported (12 to 27%) and decreasing the proportion who felt alone and anxious (27 to 15%). All professionals accessing the archive found it helpful, stating it increased empathy and understanding of parents' emotions which improved confidence that parents' needs could be met. Archives of real experiences may help parents and professionals after perinatal death. Further research is needed whether such an archive has a wider reach and accessibility than traditional support networks.